Eudemonic Well-Being Relationship with ‎Unemployment Anxiety among Graduate ‎Yarmouk University Students - Amora ‎, Tasneem; Tashtoush, Rami (Jordan Journal of Educational Sciences, 2024)
This study aimed to identify the level of eudemonic well-being and unemployment anxiety among graduate students at Yarmouk University and reveal the relationship between eudemonic well-being and unemployment anxiety. The study sample consisted of 288 male and female students who are expected to graduate; they were chosen using the available method. To achieve the objectives of the study, psychological well-being and the unemployment anxiety scale were used.The descriptive correlative approach was used. The results revealed that the level of eudemonic well-being among the graduate students was "moderate", and the level of unemployment anxiety was "high". The results also indicated a negative relationship between eudemonic well-being and unemployment anxiety. Moreover, there were statistically significant differences in the level of eudemonic well-being according to the gender variable in favor of females and in the income variable in favor of more than 800 JOD. Additionally, there were no differences due to the effects of college, grade, and place of residence. The results also showed that there were statistically significant differences in the level of unemployment anxiety based on gender (more so for men), college (more so for humanities colleges), and income (more so for those making less than 500 JOD and between 500 and 800 JOD). There were no differences based on estimation or place of residence